Inhibitory Action of Neem Aqueous Extract (Azadirachta indica A. Juss) on the Vitellogenesis of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) Ticks - Denardi, Sandra Eloisi [UNESP]; Bechara, Gervasio Henrique [UNESP]; de Oliveira, Patricia Rosa [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2011)
The present study revealed unheard of data about the action of aqueous extracts of neem leaves (Azadirachta indica) on the vitellogenesis of Rhipicephalus sanguineus ticks, proving that these extracts in 10 and 20% concentrations do not have the potential to kill the females; however, in lower concentrations (10%) provokes great morphological alterations in germinative cells such as the emergence of extended cytoplasmic vacuolization areas as well as the fragmentation of the germinal vesicle, even in those oocytes which were in initial stages of development (I-III), showing that neem is a potent agent which acts impeding one of the main metabolic stages of the ticks, i.e., the reproduction. In oocytes in final stages of development (IV-V) azadirachtin (neem's active principle) caused significant reduction in the size and quantity of proteic granules of the yolk and the inversion of their localization where the smaller granules before inside the cell (normal oocyte) were posteriorly observed in the periphery, and the bigger ones in the central region. Thus, the study showed that the alterations found both in the oocytes and in the pedicel cells indicated that azadirachtin acts on the process of tick's reproduction and signalizes that this plant can be used in the future to control ticks with the advantage of not being aggressive to nontarget organism or the environment. Furthermore, data here obtained showed that the most significant efficiency of the aqueous extract of neem is related to the concentration of 10%, proving that higher doses would not be so efficient. Microsc. Res. Tech. 74:889-899, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: Rhipicephalus sanguineus; Azadirachtin; Neem; Oocytes; Reproduction